Legal impediments to the collateralization of intellectual property in the Malaysian dual banking system - Azmi, Ida Madieha; Engku Ali, Engku Rabiah Adawiah (Asian Journal of Comparative Law, 2007)
This paper examines the legal impediments facing the acceptability of intellectual property as collateral in Malaysia. As Malaysia practices a dual banking system, conventional and Islamic, both running parallel to each other, the position of intellectual property under the Islamic banking system will also be analysed. This, in turn, requires a deeper elaboration of principles relating to collateral security or rahn in Islamic law. The paper also proceeds to explore the suitability, acceptability and practical risks of allowing intellectual property as a form of security in comparison to "physical assets".